Legal Position of Substitute Heirs in the Distribution of Inheritance: A Comparative Study of the Civil Code and the Compilation of Islamic Law - Qadriani Arifuddin (Leges Privatae, 2025)
This study examines the legal status of substitute heirs in inheritance distribution through a comparative study between the Civil Code (KUH Perdata) and the Compilation of Islamic Law (KHI). The background of the study is based on differences in the regulation and practice of inheritance distribution, particularly in terms of scope, portion size, and the legal philosophy used. The research method applied is normative juridical with a comparative approach, using analysis of laws and regulations, court decisions, and academic literature from 13 scientific journal sources. The results show that the Civil Code regulates substitute heirs with a broader scope, including lateral and upward lines, and applies the principle of equality of distribution. In contrast, the KHI limits the replacement only to a straight line downward and follows the faraidh principle that distinguishes the shares of men and women. The discussion reveals that this difference is influenced by differences in the legal philosophy of the Civil Code based on equality of rights, while the KHI is based on sharia distributive justice. The conclusion of the study confirms that although there are similarities in the recognition of the rights of substitute heirs, fundamental differences remain. Procedural harmonization between the two legal systems is necessary to provide certainty and justice in cross-jurisdictional inheritance cases in Indonesia.